1992
DOI: 10.1093/jnci/84.12.962
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Polyps to Cancer of the Large Intestine

Abstract: Our results support the suspected relationship between colorectal polyps and cancer incidence and extend the association to colorectal cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 0 publications
3
17
0
4
Order By: Relevance
“…We also found an excess of second primary colorectal cancer and of prostatic cancer following a diagnosis of colorectal cancer (Levi et al, 1993b). Data from several cancer registries (e.g., Connecticut, Hoar et al, 1985; Denmark, Lynge et al, 1985; New South Wales, Australia, McCredie et al, 1997) (predominantly colon, rectum, breast, pancreas, stomach, ovary and endometrium) has been described (Lynch and Smyrk, 1996) as part of hereditary non-polyposis colorectal cancer syndrome, but remains poorly defined (Li, 1996).To (Levi et al, 1993a(Levi et al, , 1997.After exclusion of 484 colorectal cancer cases detected at death or autopsy and of 101 cases whose colorectal cancer was synchronous (i.e., within 2 months) with another cancer, the present series comprised 5,261 colorectal cancers (World Health Organization, 1976; ICD-9 153-4) diagnosed between 1974 and 1994 and 4,300 polyps (adenomatous, ICD-O 8210/0; villous, 8261/1; and mixed type, 8263/0) The present analysis confirms, on the basis of a doubled number of cases (Levi et al, 1993a), that the incidence of cancer of the colon, stomach and, possibly, small intestine (but not rectal cancer) is increased after adenomatous polyp of the large intestine (Atkin et al, 1993;Simons et al, 1992) (Lynch and Smyrk, 1996). On account of limited study power, however, increases of less than 50% for breast, corpus uteri or prostate cannot be ruled out.…”
supporting
confidence: 74%
“…We also found an excess of second primary colorectal cancer and of prostatic cancer following a diagnosis of colorectal cancer (Levi et al, 1993b). Data from several cancer registries (e.g., Connecticut, Hoar et al, 1985; Denmark, Lynge et al, 1985; New South Wales, Australia, McCredie et al, 1997) (predominantly colon, rectum, breast, pancreas, stomach, ovary and endometrium) has been described (Lynch and Smyrk, 1996) as part of hereditary non-polyposis colorectal cancer syndrome, but remains poorly defined (Li, 1996).To (Levi et al, 1993a(Levi et al, , 1997.After exclusion of 484 colorectal cancer cases detected at death or autopsy and of 101 cases whose colorectal cancer was synchronous (i.e., within 2 months) with another cancer, the present series comprised 5,261 colorectal cancers (World Health Organization, 1976; ICD-9 153-4) diagnosed between 1974 and 1994 and 4,300 polyps (adenomatous, ICD-O 8210/0; villous, 8261/1; and mixed type, 8263/0) The present analysis confirms, on the basis of a doubled number of cases (Levi et al, 1993a), that the incidence of cancer of the colon, stomach and, possibly, small intestine (but not rectal cancer) is increased after adenomatous polyp of the large intestine (Atkin et al, 1993;Simons et al, 1992) (Lynch and Smyrk, 1996). On account of limited study power, however, increases of less than 50% for breast, corpus uteri or prostate cannot be ruled out.…”
supporting
confidence: 74%
“…10,16,[28][29][30] In some studies, but not in all, adenoma size > 10 mm, 19,21,22,24 the presence of a villous component, 12,16,22,25 or high-grade dysplasia 12,22 also were associated with adenoma recurrence. On the other hand, our study did not provide any evidence that these characteristics may increase the risk of recurrence, except for moderate/severe dysplasia, which tended to be associated with the recurrence of advanced adenomas.…”
Section: Discussionmentioning
confidence: 95%
“…Several other studies have also reported on the cancer risk after removal of adenoma. Studies reporting on cohorts of populations without surveillance have reported on an increased risk [10,11,12,13] while a reduced risk has been reported in studies with systematic surveillance after polypectomy [6,15,16,17]. Therefore, polypectomy in combination with surveillance colonoscopy and not polypectomy alone appears to reduce the risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the frequency of metachronous cancer detected upon surveillance colonoscopy after resection of colorectal cancer is comparable with the rate of cancers detected upon screening colonoscopy [8]. Studies on the risk of metachronous cancer after polypectomy have yielded discordant results: some studies have reported an increased risk [10,11,12,13,14], others have reported a reduced risk [6,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%